A community based study of NCD risk factors among adult population in Dehradun, India - Agarwal, Himanshu; Gupta, Sudhir Kumar; Negi, Kamal Singh; Jain, Kajal; Singh, Sadhna; Luthra, Megha (Indian Journal of Community Health, 2016)
Background: A Non-Communicable disease (NCD) is one which is non-infectious and non-transmissible among people. NCDs account for leading causes of death and disease burden worldwide. To decrease the burden of NCDs experts stress on the importance of prevention and control with respect to modifiable risk factors. The World Health Organization's World Health Report 2002 identified tobacco use, alcohol consumption, overweight, physical inactivity, high blood pressure and high cholesterol as the most important risk factors for NCDs.(1) Aims & Objectives: 1. To know the prevalence of risk factors leading to NCDs in the study population. 2. To know the socio-demographic correlates associated with risk factors of NCDs. 3. To suggest appropriate recommendations regarding modifiable risk factors of NCDs in study population. Material & Methods: A Cross-sectional study, Community-based study among 18+ population in field practice areas of Community Medicine Department, SGRRIM&HS, Dehradun. Sample Size: 300 each in urban and rural, total 60. Results: The prevalence of Smoking was 11.3%, Smokeless tobacco use 10.5%, Alcohol use 13.2%, Unhealthy diet 99.5%, Low physical activity 0.8%, High BMI (? 25 kg/m2) 51.2%, above normal waist-hip ratio 57.0%, Raised blood pressure 58.5% and raised blood sugar 25.2%. Conclusion: Smoking is significantly associated with age, sex and occupation. Raised blood pressure is significantly associated with age, sex and social class.